It Ends with Us - Book 1 Book 1 - Hoover, Colleen (New York : Atria Paperback, 2016)
"Lily hasnt always had it easy, but thats never stopped her from working hard for the life she wants. Shes come a long way from the small town in Maine where she grew up-- she graduated from college, moved to Boston, and started her own business. So when she feels a spark with a gorgeous neurosurgeon named Ryle Kincaid, everything in Lilys life suddenly seems almost too good to be true ... But Ryles complete aversion to relationships is disturbing. Even as Lily finds herself becoming the exception to his no dating rule, she cant help but wonder what made him that way in the first place."--
Keywords: Businesswomen -- Fiction; Neurosurgeons -- Fiction; Man-woman relationships -- Fiction; Triangles (Interpersonal relations) -- Fiction; Boston (Mass.) -- Fiction